Pengembangan Sistem Deteksi Karbon Monoksida Berbasis IoT - Salman Al Farizi; Eko Sakti Pramukantoro; Heru Nurwarsito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Health factors become one of the important role in improving the quality of human life. Low air quality in densely populated cities can lead to a significant drop in health care. Carbon monoxide as the main pollutant of the capital deserves more spotlight in its handling. This research focuses on indoor detection of carbon monoxide gas. In the previous research, IoT middleware was developed which can solve syntactical interoperability problem. This developing system will be integrated with existing IOT middleware. To facilitate user interaction, the development is done by making apps for smart phones based on the Android operating system that provide a user-friendly interface and can provide notifications in the app if the sensor readout value exceeds the safe limit. There are several parameters to test the developed system, including integration, context-awareness testing, and Quality of Service (QoS). Based on the results of testing on this system, it was found that the developed system has perfect data integrity. On the other hand, developed systems meet the rules of context-awareness computing.